F404 Engine performance simulation - Ho, Peng Yip. (2008)
This report documents the development of an aircraft gas turbine engine performance computation software. The firstpart describes the analysis necessaryin order to obtain the component data needed by the software. And the second part details the design features and operating characteristics of the software.